2022
DOI: 10.3390/jpm12101580
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Periodontal Implications of Hepatitis Type B and D. Current State of Knowledge and Future Perspectives

Abstract: Periodontitis is characterized by low-grade inflammation of the periodontal tissues, the structures that support and connect the teeth to the maxilla and mandible. This inflammation is caused by the accumulation of subgingival bacterial biofilm and gradually leads to the extensive damage of these tissues and the consequent loss of teeth. Hepatitis B is a major global health concern; infection with the hepatitis B virus causes significant inflammation of the liver and the possibility of its gradual evolution to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Dental plaque and calculus are the major cause of gingivitis and periodontitis in our population. Though, periodontal disease is common in hepatitis patients 10,11 . Very few cases of Oral lichen planus show that it does not have a strong link with hepatitis but there is chance of certain changes such as formation of immune cells due to chronic hepatitis which may trigger OLP in these patients 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental plaque and calculus are the major cause of gingivitis and periodontitis in our population. Though, periodontal disease is common in hepatitis patients 10,11 . Very few cases of Oral lichen planus show that it does not have a strong link with hepatitis but there is chance of certain changes such as formation of immune cells due to chronic hepatitis which may trigger OLP in these patients 19 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been noticed that approximately 75% of the HCV cases may present with Extrahepatic manifestations (EHM), the majority being oral manifestations 9 . A high rate of detection of Hepatitis B and C was noticed in patients with periodontal diseases 10,11 . While several studies have shown a positive correlation of Lichen Planus with Hepatitis C 12,13 .…”
Section: Introductionmentioning
confidence: 99%